Lord of the Three in One The Spread of a Cult in Southeast China - Dean, Kenneth (Princeton University Press, 2023)
Lin Zhao'en (1517-1598) set out to popularize Confucianism by combining Confucian studies with Daoist inner alchemical techniques and Buddhist Chan philosophy into something he called the Three in One Teachings. Despite periods of clandestine activity since its inception, the Three in One cult has undergone a remarkable revival in post-Mao China: today Lin is worshipped throughout Southeast China and Southeast Asia as Lord of the Three in One in over a thousand temples by tens of thousands of cult initiates. Many of the temples have been restored since 1979, when China began to experience an explosive resurgence of popular culture and religion. In this book, based on ten years of field work, Kenneth Dean vividly documents the reemergence of this cult, which seeks to transmit a universal vision of truth yet retains a strong local appeal through its healing rituals and spirit mediumism. Although the Chinese government still tries to suppress these resurgences in the interest of modernization, the cult's locally based networks appear in this account as unstoppable social forces.Dean explores the organization and transmission of the Three in One's unique cultural vision, the reception of this vision, and the construction of subjectivity within a vibrant ritual tradition. Outlining such features as inner alchemical meditation, scripture and iconography, ritual practice, and spirit mediumism, he demonstrates the cult's transformative potential as well as its contemporaneity and dynamism. Rural Chinese popular culture as a whole emerges here as highly complex and always evolving--traditional and resilient